2018
DOI: 10.1103/physrevb.97.245134
|View full text |Cite
|
Sign up to set email alerts
|

Importance of van der Waals interactions and cation-anion coupling in an organic quantum spin liquid

Abstract: The Mott insulator β ′ -EtMe3Sb[Pd(dmit)2]2 belongs to a class of charge transfer solids with highly-frustrated triangular lattice of S = 1/2 molecular dimers and a quantum-spin-liquid ground state. Our experimental and ab initio theoretical studies show the fingerprints of strong correlations and disorder, important role of cation-dimer bonding in charge redistribution, no sign of intra-and inter-dimer dipoles, and the decisive van der Waals contribution to inter-dimer interactions and the ground state struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Below approximately 200 cm −1 , however, the optical conductivity exceeds the power-law extrapolation considerably, giving evidence for an additional contribution to the electrodynamic response. At much lower frequencies, σ 1 (ω) gradually levels off toward the dielectric data [117], comparable to what is plotted in figure 8 for κ-(BEDT--TTF) 2 Cu 2 (CN) 3 . The transition regime is consistent with a σ 1 (ω) ∝ ω 2 behavior as suggested by Ng and Lee [62], that catches up the interpolated value of the correlated electrons rather quickly.…”
Section: Spinon Contributionsupporting
confidence: 79%
“…Below approximately 200 cm −1 , however, the optical conductivity exceeds the power-law extrapolation considerably, giving evidence for an additional contribution to the electrodynamic response. At much lower frequencies, σ 1 (ω) gradually levels off toward the dielectric data [117], comparable to what is plotted in figure 8 for κ-(BEDT--TTF) 2 Cu 2 (CN) 3 . The transition regime is consistent with a σ 1 (ω) ∝ ω 2 behavior as suggested by Ng and Lee [62], that catches up the interpolated value of the correlated electrons rather quickly.…”
Section: Spinon Contributionsupporting
confidence: 79%
“…An anomalous dielectric peak shows up as an ubiquitous property independent of the nature of the ground state in the spin sector [458,523,576,608,610,620] The relaxor-type dielectric response suggests a short-range ferroelectric-like order [576,621] and the existence of domains of low symmetry equivalent with the average high symmetry, in accord with density functional (DFT) calculations and structural refinements [71,72,523,556,620]. However, both spectroscopic [490,523,610,620] and structural measurements [71,72] consistently demonstrate the equally distributed charge in quantum spin liquid compounds. Moreover, the persistence of strong quantum fluctuations due to charge or dipolar fluctuations in the kHz-MHz frequency range is unlikely because no Barrett-like behavior of the dielectric constant [cf.…”
Section: Ferroelectric-like Signatures In Quantum Spin Liquid and Antmentioning
confidence: 61%
“…In the BEDT-TTF-based quantum spin liquids, this structure originates from the cyanide groups located at the inversion centers bridging the polymeric CuCN/AgCN chains in the anionic layer. In the β -EtMe 3 Sb[Pd(dmit) 2 ] 2 with quantum spin liquid ground state, disorder occurs due to two equally probable orientations of the Et groups (static disorder) and to internal rotational degrees of freedom of the Me groups (dynamic disorder); both Et and Me groups reside in the non-conducting cations [620]. Interestingly, a quantum-spin-liquid state is not established in β -Me 4 P[Pd(dmit) 2 ] 2 and β -Me 4 Sb[Pd(dmit) 2 ] 2 : here static disorder is absent, but dynamic disorder is still present and causes a relaxor peak in ε (T ) [621].…”
Section: Ferroelectric-like Signatures In Quantum Spin Liquid and Antmentioning
confidence: 99%
“…The previous DFT studies on different organic charge-transfer salts have neither included nor discussed the van der Waals (vdW) interactions at all [64][65][66][67][68][69][70]. The only exception is found in our work [23,24,39].…”
Section: Van De Waals Interactions In κ-(Bedt-ttf) 2 X; X = Cu[n(cn) mentioning
confidence: 72%
“…The role of random disorder in this competition may also be important, as indicated by an experimental study on κ-Cl showing that X-rays suppress magnetic order and allow a spin liquid to form [38]. Finally, we have recently suggested that the non-conducting anions which contain frustration and disorder in the organic spin liquids may be a critical ingredient needed for the prevalence of quantum spin liquid over magnetic ordering [39].…”
Section: Introductionmentioning
confidence: 98%